Pain Management in Nursing Home Residents with Cancer. Issue 4 (April 2015) - Pimentel, Camilla B.; Briesacher, Becky A.; Gurwitz, Jerry H.; Rosen, Allison B.; Pimentel, Marc T.; Lapane, Kate L.
Abstract : Objectives: To assess improvements in pain management of nursing home (NH) residents with cancer since the implementation of pain management quality indicators. Design: Cross‐sectional. Setting: One thousand three hundred eighty‐two U.S. NHs (N = 1, 382). Participants: Newly admitted, Medicare‐eligible NH residents with cancer (N = 8, 094). Measurements: Nationwide data on NH resident health from Minimum Data Set 2.0 linked to all‐payer pharmacy dispensing records (February 2006–June 2007) were used to determine prevalence of pain, including frequency and intensity, and receipt of nonopioid and opioid analgesics. Multinomial logistic regression was used to evaluate resident‐level correlates of pain and binomial logistic regression to identify correlates of untreated pain. Results: More than 65% of NH residents with cancer had any pain (28.3% daily, 37.3% <daily), 13.5% of whom had severe and 61.3% had moderate pain. Women; residents admitted from acute care or who were bedfast; and those with compromised activities of daily living, depressed mood, an indwelling catheter, or a terminal prognosis were more likely to have pain. More than 17% of residents in daily pain (95% confidence interval (CI) = 16.0–19.1%) received no analgesics, including 11.7% with daily severe pain (95% CI = 8.9–14.5%) and 16.9% with daily moderate pain (95% CI = 15.1–18.8%). Treatment was negatively associated with age of 85 and older (adjusted OR (aOR) = 0.67, 95% CI = 0.55–0.81 vs aged 65–74), cognitive impairment (aOR = 0.71, 95% CI = 0.61–0.82), presence of feeding tube (aOR = 0.77, 95% CI = 0.60–0.99), and restraints (aOR = 0.50, 95% CI = 0.31–0.82). Conclusion: Untreated pain is still common in NH residents with cancer and persists despite pain management quality indicators.